Mendívil, Julio. En contra de la música. Buenos Aires: Gourmet Musical Ediciones, 2016, 192 pp. - Elias Llanos, Fernando (2018)
The book covers several current and controversial topics that music causes in our day-to-day life: the concept of music and its pretended universality, its relationship with identity - national and global - and the ways in which it operates, for better or worse, in a society mediated by information technologies.